Cocoa in Samoa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'The Cocoa Book', 199O, 83pp IRETA Communication Support Centre USP Alafua Campus, Private Mail Bag Apia, WESTERN SAMOA